THE DEVELOPMENT OF CREATIVE THINKING ABILITY IN THAI LANGUAGE CLASSES WITH OPEN LEARNING MANAGEMENT - Chumueang, Jiruttiporn; Pinagalung, Sungwean (Journal of Graduate MCU KhonKaen Campus, 2021)
The research on the development of creative thinking ability in Thai language classes with open learning management is the development of creative thinking ability of Prathom 3 students in Thai language classes. The research is able to develop students to have a various ways of thinking, imagination, creative thinking, and a variety of creative opinions without being told right or wrong because the open learning management is a teaching method that allows students to think in various ways. It is an open-ended thinking, thinking outside the box without limitations. Students can think of new things without being told right or wrong. Students can rationally practice creative thinking and develop creative thinking. This method encourages students to practice using their imagination, broad thinking, and various ways of thinking, which results in students having a wide range of imagination and being able to think and create new things through imagination and experiences from the practice of creative thinking. The teachers must use friendly teaching methods with students to create a safe and friendly atmosphere that is beneficial to the use of creativity and allows students to be confident to think, imagine, and have their own opinions without being told right and wrong. Students will use their imagination as much as possible. The students’ creative thinking abilities will differ depending on their experiences, intelligence, motivation, and emotions. It is an open-ended response with a variety of answers. The open learning management is the teaching and learning management that focuses on students having a wide range of experiences with open-ended problems with various types of answers from many thinking processes that students think from their own imaginations, not from the teachers who provide the answers. This method allows students to think systematically, rationally, and creatively. For the development of creative thinking ability in Thai language classes with the learning management, the results showed that the development of creative thinking ability in Thai language classes with the open learning management was able to develop students to have a wide range of thinking abilities. The result of the test of the students’ creative thinking ability in Thai language classes showed a higher score of the post-test than the pre-test because the open learning management helps students to practice solving open-ended problems, practice thinking and imagination skills, have their own ideas, be confident to express opinions, and find a solution to various types of problems. Imagination and creative thinking abilities depend on the ability, knowledge, intelligence, and experiences of the students. The teachers must provide a friendly teaching atmosphere to help the students to have no pressures and be confident to definitely express opinions and practice students to try perform, think, and imagine by themselves. Therefore, the students will have better skills in creative thinking.